2023
DOI: 10.3390/ani13182821
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Efficacy of Complete Blood Count Indices for Assessing the Presence and the Progression of Myxomatous Mitral Valve Disease in Dogs

Min-Jung Jung,
Jung-Hyun Kim

Abstract: This study investigated the complete blood count (CBC) indices, including neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and platelet-to-lymphocyte ratio (PLR) in dogs with myxomatous mitral valve disease (MMVD) and analyzed their correlation with conventional biomarkers, as well as the effect of CBC indices on survival time in dogs with MMVD. Medical records of 75 healthy controls and 249 dogs with MMVD from March 2015 to October 2022 were analyzed. The NLR, MLR, and PLR were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In this study, correlations showed the presence of relationships between CBC indices, particularly NLR and RDW/PLT ratio, and serum levels of proin ammatory and anti-oxidant markers. Thus, NLR and RDW/PLT may be associated with end-stage HF, due to their potential roles in cellular immune and in ammatory mechanisms in development and progression of MMVD in dogs (Jung and Kim 2023). This observation could be supported by our previous ndings including those in ammatory chemokines (KC-Like, and MCP-1, etc.)…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, correlations showed the presence of relationships between CBC indices, particularly NLR and RDW/PLT ratio, and serum levels of proin ammatory and anti-oxidant markers. Thus, NLR and RDW/PLT may be associated with end-stage HF, due to their potential roles in cellular immune and in ammatory mechanisms in development and progression of MMVD in dogs (Jung and Kim 2023). This observation could be supported by our previous ndings including those in ammatory chemokines (KC-Like, and MCP-1, etc.)…”
Section: Discussionsupporting
confidence: 77%
“…The dogs were staged according to the ACVIM classi cation of HF (Keene et al 2019;Atkins et al 2009); stage A (healthy/controls, n = 8), stage B2 (n = 6), stage C (n = 10), and stage D (n = 5). Criteria used for classifying groups and some of the clinical data (physical, hematological and serum biochemistry examinations and cardiac imaging ndings) were already detailed in our (Rubio et al 2020;Saril et al 2022) and other previously published papers (DeProspera et al 2023; Jung et al 2023). Brie y, MMVD B2 was de ned when a dog did not show clinical signs relating to cardiopulmonary disease, in conjunctive with structural remodeling of the heart meaning the presence of cardiomegaly radiographically, and echocardiographic evidence of left atrial and/or left ventricular dilatation.…”
Section: Study Materialsmentioning
confidence: 99%